XRF geochemistry for Site IODP 379-U1533 - Becky Hopkins; Chuang Xuan; Claus-Dieter Hillenbrand; Tim E van Peer; Yuxi Jin; Thomas Frederichs; Liang Gao; Steven M Bohaty (PANGAEA, 2024)
Analysis of IODP Site 379-U1533 natural log of barium (30 kV) and rubidium (50 kV) measured on Avaatech X-ray fluorescence (XRF) core scanner at International Ocean Discovery Program (IODP), College Station, Texas in 2019. Measurements were completed on archive halves of core sections at 2-cm resolution in order to better understand the elemental composition of the sediment and to construct an age model. ln(Ba/Rb) was used as a proxy for palaeoproductivity, which south of the Antarctic Polar Front is controlled be spring/summer sea ice extent. Measurements cover the Plio-/Pleistocene period.